2017
DOI: 10.4239/wjd.v8.i7.374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on adiposity and metabolic profiles: A prospective cohort study in Middle-Eastern patients

Abstract: AIMTo investigate changes in adiposity and cardio-metabolic risk profile following Roux-en-Y gastric bypass in patients of Middle Eastern ethnicity with severe obesity.METHODSThis prospective cohort study involved 92 patients who met the indications of bariatric surgery. Post-procedure markers of obesity and cardiometabolic profile were monitored regularly for a year.RESULTSMean body mass index decreased by 29.5% from 41.9 to 29.5 kg/m2 between baseline and 12-mo follow-up, while mean fat mass decreased by 45.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Mazidi et al [25] found a marked effect of bariatric surgery on adiposity and metabolic profile, which was detected by a reduction in BMI and body fat after one year postoperatively, a marked improvement in HDL, and a reduction in cardiovascular risk factors such as total cholesterol level, triglycerides, and LDL level.…”
Section: Discussionmentioning
confidence: 99%
“…Mazidi et al [25] found a marked effect of bariatric surgery on adiposity and metabolic profile, which was detected by a reduction in BMI and body fat after one year postoperatively, a marked improvement in HDL, and a reduction in cardiovascular risk factors such as total cholesterol level, triglycerides, and LDL level.…”
Section: Discussionmentioning
confidence: 99%